RELEVANSI PRESTASI BELAJAR SEBAGAI PREDIKTOR PENALARAN MORALITAS (Studi Kasus di SMA Negeri 5 Samarinda) - Siti Murti; Heryanto Heryanto (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2019)
The purpose of this study is to analyze the relevance of morality with student achievement so that its contribution to learning achievement is known. This research includes the type of verification research conducted through data collection in the field using survey methods. The unit of analysis was taken using a simple random sampling technique. Data were collected through observation, interviews, questionnaires, and documentation. This study consisted of two variables, namely morality as the independent variable, and student learning achievement as the dependent variable. The results of the study show that the correlation between moral reasoning and student achievement is 0.683 (the degree of relationship is strong). This means that students' morality reasoning is 46.65% determined by learning achievement factors, and 53.35% is determined by other factors.